Factors Shaping the Morphology in Sol‐Gel Derived Mesoporous Zinc Titanate Films: Unveiling the Role of Precursor Competition and Concentration - Li, Yanan; Li, Nian; Harder, Constantin; Yin, Shanshan; Bulut, Yusuf; Vagias, Apostolos; Schneider, Peter M.; Chen, Wei; Roth, Stephan V.; Bandarenka, Aliaksandr S.; Müller‐Buschbaum, Peter (Advanced materials interfaces, 2024)
Zinc titanate films with mesoporous structures have widespread applications ranging from sensors to supercapacitors and bio‐devices owing to their photoelectric properties and specific surface area. The present work investigates the morphology of mesoporous zinc titanate films obtained by calcination of hybrid thin films containing polymer templates and precursor mixtures of zinc acetate dihydrate (ZAD) and titanium isopropoxide (TTIP). ZnO and TiO2 films are fabricated for reference. The influences of hydrochloric acid contents (HCl), the ratios of ZAD and TTIP, and the solution concentrations on the film morphologies are studied. The amphiphilic diblock copolymer, polystyrene‐block‐polyethylene oxide (PS‐b‐PEO), plays the role of a structure directing template, as it self‐assembles into micelles in a solvent‐acid mixture of N, N‐dimethylformamide (DMF) and HCl. Thin films are prepared with spin‐coating and subsequent calcination. Adjusting the ratio of TTIP and ZAD leads to the structure evolution from order to disorder in a film. It depends on the hydrolysis and condensation processes of the precursors, providing different time‐to‐growth processes to control the film morphologies. An increase in solution concentration enhances the surface coverage. As probed with grazing‐incidence small‐angle X‐ray scattering, the inner structures are larger than the surface structures seen in scanning electron microscopy. The influences of the hydrochloric acid contents (HCl), the ratios of the two precursors, and the solution concentration on film morphology of mesoporous zinc titanate films obtained by calcination of hybrid thin films are studied. An increase in HCl content inhibits the rate of precursor hydrolysis, enlarging the parameter window for the block copolymer templating.